Effect of Chitosan and Chlorocholine Chloride on the Minituberization of Cocoyam (Xanthosoma sagittifolium L. Schott) - Carole, MEJANE EKANE; Carole, Djeuani Astride; FOTSO, FOTSO; Pierre, Djoucgoue François; Denis, Omokolo NDOUMOU (International Journal of Environment, Agriculture and Biotechnology, 2019)
This study was carried out in order to evaluate the effect of chitosan (1, 2 and 3gL-1) and chlorocholine chloride (5, 10 and 15mgL-1) on the minituberization of cocoyam (Xanthosoma sagittifolium). Results showed that both phytohormones reduced the growth cycle of cocoyam from 6 to 5months with the best results obtained at the concentrations 2gL-1 and 15mgL-1 for chitosan (CTH) and chlorocholine chloride (CCC) respectively. The average number of leaves was greater in CTH at 2gL-1 (3.80±1.40) and 10mgL-1(3.60±0.70) for CCC. The optimal height of the plant for CTH was obtained at 1gL-1 (17.87±5.47 cm) and 15mgL-1 (21.15±1.99 cm) for CCC. The average leaves surface was greater at 1gL-1 (36.39±17.02 cm2) for CTH and 15mgL-1 (25.87±5.62 cm2) for CCC. The number of minitubers harvested as well as the percentage of tuberization was maximum with 29minitubers at 2gL-1 and 23 for 15mgL-1.The size of the minitubers was best at 3gL-1(2.60±0.26 cm) for CTH and 10mgL-1 (0.56±0.27 cm) for CCC. The mass of the minitubers increased with best results obtained at 3gL-1(2.80±0.84g) and at 10mgL-1 (0.20±0.36g) for CTH and CCC respectively.